Optimization of snatch lift by using genetic algorithm - Nejadian, S. L.; Rostami, M. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Barbell trajectory during weightlifting has been investigated by many researchers like Garhammer (2001). Some motion patterns was categorized as optimizedone because of the percentage of their owners` success. We believe that in optimizing the barbell trajectory we should consider the mechanical principles. We formulate a 5-link (shin, thigh, trunk, upper arm and forearm) dynamic model, according to anthropometric data, to predict the optimum (minimum torque) barbell trajectory by using genetic algorithm (GA).